2007
DOI: 10.1111/j.1469-1795.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Malathion applied at standard rates reduces fledgling condition and adult male survival in a wild lesser kestrel population

Abstract: The lesser kestrel Falco naumanni is a globally threatened colonial bird that has suffered a generalized population decline in Europe. Recent studies have suggested that the land-use changes linked to agriculture intensification are the main factors accounting for the population regression. However, there has been little analysis of the role of pesticide applications. In this study, we examined the consequences of a malathion treatment in a wild population of lesser kestrels, specifically its effects on breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…great bustard Otis tarda and little bustards Tetrax tetrax ); (3) preventing the application of highly toxic pesticides that may affect both directly and/or indirectly (by reducing prey abundance) to lesser kestrel (e.g. Ortego et al ., 2007); (4) implementing monitoring programmes of summer roosts of lesser kestrel and the investigation of other premigratory areas.…”
Section: Discussionmentioning
confidence: 99%
“…great bustard Otis tarda and little bustards Tetrax tetrax ); (3) preventing the application of highly toxic pesticides that may affect both directly and/or indirectly (by reducing prey abundance) to lesser kestrel (e.g. Ortego et al ., 2007); (4) implementing monitoring programmes of summer roosts of lesser kestrel and the investigation of other premigratory areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, we have been monitoring the largest Sicilian population of lesser kestrels nesting in the Gela Plain (Sicily, 37°07'N, 14°19'E; [28, 34], an agricultural landscape extended over 450 km 2 with a mosaic of pseudo-steppes [35]. As in most avian species [10, 11], seasonality affects kestrel reproductive outcome, with late kestrel breeders being less successful than the early ones (unpublished results). Several farmhouses and rural buildings are scattered across the plain with each hosting one kestrel colony.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to nest characteristics, behavioral traits, such as nest site selection, may represent a valid measure to adopt for mitigating adverse nest conditions when suitable microenviromental features are available [10, 11]. Selection of optimal nest sites are expected to be under strong selection pressure [22, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Insecticide spraying during the yellowhammer breeding season (June/July) may be more detrimental than multiple spraying at other times (Morris et al, 2005). In southern Europe, recent studies have shown that organophosphorous pesticides applied at standard rates might disrupt populations of threatened invertebrate-feeding birds such as the lesser kestrel, due to direct toxic effects and the reduction in invertebrate prey availability (Ortego et al, 2007), though such effects may not be widespread (Vergara et al, 2008). The incidence of poisoning of wild mammals by pesticides decreased in the UK (Barnett et al, 2006).…”
Section: Arable Inputsmentioning
confidence: 98%